Symbolization of Sincerity in Suluk Saridin as a means of Getting Closer to God - Jamil, Miftahul; Darmayanti, Rossyana Fani; Oktavia, Nabila; Ismail, Kelvin; Fauziyah, Anita Nisa'i; Utami, Respati Retno (CV. Publikasi Indonesia, 2024)
This research is motivated by the phenomenon of corruption and crime that is increasingly becoming in society based on the distance of servants from God. therefore, we want to contribute to solving the phenomenon by providing solutions from suluk Saridin Yaang we researched this. In this research, we used the semiotic theory of Ferdinand D Saussure to find the data in the suluk Saridin, we chose this theory because. In this theory, it suggests that there are markers and markers then the method we do is a qualitative research method with data collection techniques that use interview techniques and literature studies. As a result of this research we found a symbolization of the sincerity that exists in zakat in suluk Saridin as a means to get closer to God.